1973
DOI: 10.1172/jci107253
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Spread and Longitudinal Dissociation in the Distal A-V Conducting System

Abstract: Isolated preparations of portions of the canine intraventricular conducting system were studied by microelectrode techniques in order to determine the nature of transverse spread and longitudinal dissociation of impulses in bundle branches and false tendons. Driving stimuli were delivered to an eccentric location on normal conducting tissue, and the arrival times of the propagating impulses were mapped along the length and width of the bundle branch, or along the false tendon ipsilateral and contralateral to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…After equilibration to a solution, the conduction time remained stable at the same values without change. Myerburg et al (5) reported that there is dissociation of transverse and longitudinal spread of excitation in the false tendon which may distort conduction time measurement, but the placing of stimu lating and recording electrodes and the stimulus strength used in this study may be enough to eliminate the dissociation of excitation.…”
Section: Methodsmentioning
confidence: 72%
“…After equilibration to a solution, the conduction time remained stable at the same values without change. Myerburg et al (5) reported that there is dissociation of transverse and longitudinal spread of excitation in the false tendon which may distort conduction time measurement, but the placing of stimu lating and recording electrodes and the stimulus strength used in this study may be enough to eliminate the dissociation of excitation.…”
Section: Methodsmentioning
confidence: 72%
“…This selection process was carried out in order to have a population of AMI cells which had resting potentials and upstroke velocities comparable to those of healed cells from HMI preparations. Standard microelectrode techniques, previously reported in detail, were used (Myerburg et al, , 1973.…”
Section: Methodsmentioning
confidence: 99%
“…Premature stimuli were delivered at 2.0 times late diastolic threshold strength, and diastole was scanned as previously reported (Myerburg et al, , 1972(Myerburg et al, , 1973. In those preparations in which it was not possible to initiate sustained ventricular activity by premature stimulation, we determined the effects of drug on action potential duration, local refractory period, upstroke velocity, and resting membrane potential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent data in animal experiments suggests that longitudinal dissociation occurs in the intraventricular conduction system. [22][23][24][25] In figure 5, …”
Section: Mechanism Of Paired Extrasystolesmentioning
confidence: 99%